Prevalence and risk factors of hypertension among adults aged 25-64 years in a rural area of Thrissur in Kerala - Simon, Catherine; C. R., Saju; Binu, Jeffy (International Journal Of Community Medicine And Public Health, 2017)
Background: Lifestyle changes have fuelled the epidemic of obesity, diabetes, hypertension (HTN), dyslipidemia and cardiovascular diseases. Hypertension is a global public health problem Even though it can be controlled by early diagnosis, lifestyle modifications and adequate treatment; many remain unaware of their hypertension, especially in rural areas where not many studies have been done. The objective of this study was to determine the prevalence and risk factors of hypertension among adults in rural Kerala. Methods: A community-based cross-sectional study was conducted from December 2011 to May 2012 in the rural field practice area of Amala Institute of Medical Sciences, Thrissur. 423 adults, aged 25–64 years, were selected by multi-stage sampling. An interview was conducted using a pretested proforma and anthropometric measurements were recorded using standard guidelines. Diagnosis of hypertension was based on Joint National Committee (JNC) VII guidelines that included both new and previously diagnosed cases (on anti-hypertensive treatment) of hypertension (Systolic BP >140mmHg and/or Diastolic BP >90mmHg). Results: Among the 155 males and 268 females in this study, the prevalence of HTN was 43.3%, of which 98 (53.6%) were previously diagnosed hypertensives and 85 (46.4%) new HTN cases. In the multivariate analysis, the significant risk factors of HTN were age Adjusted Odds Ratio (AOR)=2.03, (95% CI=1.48-2.79), p=0.001, male sex AOR=3.65, (95% CI=1.55-8.62) p=0.001, central obesity or waist-hip ratio AOR=23.78,(95% CI =4.47-126.42), p=0.001, sedentary lifestyle AOR=2.96, (95% CI=1.48-5.90), p=0.001, high salt intake AOR=37.37,( 95% CI=18.04-77.45), p=0.001 and current smoking AOR=3.25, (95% CI =1.15-9.24), p= 0.001. Conclusions: In this study, the prevalence of hypertension was 43.3%. Pre-hypertension was found among 26.5% of the study population. The risk factors associated with HTN were male gender, increasing age, central obesity, sedentary lifestyle, excess salt intake and current smoking.